The Eclipse I Call Father : Essays on Absence - Axelrod, David, 1958- (Book collections on Project MUSE., 2019)
"A collection of essays exploring the concept of absence, ranging across topics as diverse as marriage, Japanese poetry, Craftsman design, Old English riddles, racism, extinction, fatherhood, mountaineering, predatory mega-fauna, street fighting, trains, the Great Depression, and the effects of climate change"--